Native Morphology of Influenza Virions - Noda, Takeshi (Frontiers in Microbiology, 2012)
Influenza A virus is an enveloped virus with a segmented, single-strand, negative-sense RNA genome. Its virions show spherical or filamentous shapes of about 100 nm in diameter and occasionally irregular morphology, which exemplifies the pleomorphic nature of these virions. Each viral RNA segment (vRNA) forms a ribonucleoprotein complex (RNP), along with an RNA-dependent RNA polymerase complex and multiple copies of nucleoproteins; the RNPs reside in the enveloped virions. Here, we focus on electron microscopic analyses of influenza virions and RNPs. Based on the morphological and structural observations obtained by using electron microscopic techniques, we present a model of the native morphology of the influenza virion.